La Aparición de la Antropología Literaria Chilena - Alvarado, Miguel (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
This article describes the new style of writing appearing in Chile from the 1980s. This kind of work, so called "Chilean Literature Anthropology", attempts to combine science with literary resources.